Simulating the Monty Hall problem in a DNA sequencing machine. (December 2019) - Mamet, Noam; Harari, Gil; Zamir, Adva; Bachelet, Ido
Graphical abstract: Highlights: The Monty Hall problem has a counter-intuitive yet provably correct answer. We simulate and prove the Monty Hall solution in a DNA sequencing machine. Illumina sequencing enables billions of operations in a single simulation run. Abstract: The Monty Hall problem is a decision problem with an answer that is surprisingly counter-intuitive yet provably correct. Here we simulate and prove this decision in a high-throughput DNA sequencing machine, using a simple encoding. All possible scenarios are represented by DNA oligonucleotides, and gameplay decisions are implemented by sequencing these oligonucleotides from specific positions, with a single run simulating more than 12, 000, 000 independent games. This work highlights high-throughput DNA sequencing as a new tool that could extend existing capabilities and enable new encoding schemes for problems in DNA computing.